Renewable Energy Financing with a Sustainable Financial System Following the 2008 Financial Crisis in Developing Countries - (:unkn) unknown (SPRINGER INTERNATIONAL PUBLISHING AG, 2017)
Unusual financial market conditions have affected the flow of capital and debt investment into renewable energy projects all over the world as a result of the 2008 financial crisis. The crisis collapsed trade and financial systems, decreased the movement of capital flows, and caused lower growth and inflation as well as tighter credit, lower profitability, and declining demand. The crisis spilled over from advanced economies to emerging and developing countries and the financial system in the world has deteriorated after the crisis. Financial sector development and sustainability have an important role at the renewable energy financing. Although a well-developed financial sector was said to support economic growth and stability, the crisis reminded that advanced financial systems could pose a threat to all the economy. Policy makers and international regulators have worked to assure financial sustainability, prevent global crises and encourage fair global competition in the markets during and after the crisis. The main purpose of this chapter is to define the meaning of the sustainable financial system and to analyse how the renewable energy investments were affected since the beginning of the crisis in developing countries. In the light of the literature survey, this chapter discusses renewable energy financing with a sustainable financial system following the crisis in developing countries.